Tips and Tricks in Laparoscopic Urology - Kumar, Udaya; Gill, Inderbir S. (Springer London : Imprint: Springer, 2007)
This book is written by world leaders in laparoscopic urology from various teaching urological institutions in the US, Europe and Japan who have contributed their tips and tricks in performing the various urologic procedures. Each topic is limited to a few pages to produce a small and easy-to-read book.The book is extensively illustrated with line diagrams which are self-explanatory and greatly enhance the understanding of various techniques, such as position of laparoscopic ports or technique of throwing a laparoscopic stitch. Essential for urology residents, fellows, and practicing urologists, the book provides information that will be extremely useful in the performance of routine and advanced laparoscopic surgery, as well as when particular situations or difficult moments are encountered during surgery. While many journal articles may outline one author's preference for a certain technique or trick, until now, there has been no compilation of the techniques of several authors.This handbook of tips and tricks from multiple specialists will be invaluable to residents and urologists already practicing laparoscopy.